Investigating the impact of growth temperature on WS2 thin film - Md Khan Sobayel Rafiq,; Afida Ayob,; Badariah Bais,; Md Akhtaruzzaman,; Nowshad Amin, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Radio-frequency (RF) Magnetron Sputtering was used to deposit thin tungsten di sulfide (WS2 ) films on top of soda lime glass substrates. Deposition temperature of RF magnetron sputtering was varied from room temperature (RT) to 200o C with 50o C interval to investigate the impact on film characteristics as well as to optimize for suitable application in thin film solar cells. Structural and opto-electronic properties of as-grown films were investigated and analyzed for different growth temperatures. All the WS2 films exhibit granular structure consist of rhombohedral phase with a strong preferential orientation towards (101) crystal plane. Optical bandgaps are ranged from 1.73 eV to 2.3 eV for different growth temperatures. As-grown films show higher carrier concentration with n-type conductivity. Polycrystalline ultra-thin WS2 film with bandgap of 2.4 eV, carrier concentration of 2.28 X 1017 cm-3 and resistivity of 1.52 Ω-cm were successfully achieved at 50o C with 50 W RF power that can be employed as window layers in thin film solar cells.